Synthesis and Biological Evaluation of Phosphate Prodrugs of 4-Phospho-d -erythronohydroxamic Acid, an Inhibitor of 6-Phosphogluconate Dehydrogenase - Ruda, Gian Filippo (WILEY-VCH Verlag, 2007)
We have previously reported the discovery of potent and selective inhibitors of 6-phosphogluconate dehydrogenase, the third enzyme of the phosphate pentose pathway, from Trypanosoma brucei, the causative organism of human African trypanosomiasis. These inhibitors were charged phosphate derivatives with restricted capacity to enter cells. Herein, we report the synthesis of five different classes of prodrugs: phosphoramidate; bis-S-acyl thioethyl esters (bis-SATE); bis-pivaloxymethyl (bis-POM); CycloSaligenyl; and phenyl, S-acyl thioethyl mixed phosphate esters (mix-SATE). Prodrugs were studied for stability and activity against the intact parasites. Most prodrugs caused inhibition of the growth of the parasites. The activity of the prodrugs against the parasites appeared to be related to their stability in aqueous buffer.